Plasmonic computing of spatial differentiation - Tengfeng Zhu (Nature Portfolio, 2017)
For specific problems, analog optical computing can be faster and more computationally efficient than digital methods. Here, Zhuet al. simplify the often metamaterial-based approach to a single thin metal film, with which they demonstrate spatial differentiation.